Graph drawing and network visualization : 24th International Symposium, GD 2016, Athens, Greece, September 19-21, 2016, revised selected papers /: 24th International Symposium, GD 2016, Athens, Greece, September 19-21, 2016, revised selected papers. (2019) - Unknown
No abstract available